RANCANG BANGUN SISTEM TRANSMISI PADA MESIN PENCETAK BRIKET BATOK KELAPA SKALA USAHA MIKRO KECIL DAN MENENGAH - Hakim, Muhammad Kamalul; Apnena, Riri Damayanti (Jurnal Mahasiswa Terapan; Vol 1 No 1 (2024): Jurnal Mahasiswa Terapan, 2024)
This research is entitled "Design and Construction of a Transmission System for a Coconut Shell Briquette Printing Machine on a Micro, Small and Medium Enterprise (UMKM) Scale". Indonesia is the largest coconut producer in the world, producing 19 million tons of coconut (31% of the world's total coconut production) and has a coconut plantation area of ​​3.08 million Ha. The main driver of this charcoal briquette printing machine uses a single phase electric motor with a power specification of 550 watts, with a rotation of 1390 rpm, a voltage of 220 volts, which produces a torque of 4,976 Nm. In 1 hour of operation, the charcoal briquette printing machine is capable of printing 675 charcoal brickets with a quantity of 45 kg of charcoal powder.